Self-reported food safety knowledge and practices of Lebanese food handlers in Lebanese households. Issue 3 (5th March 2018) - Hassan, Hussein F.; Dimassi, Hani; Karam, Zeina Nakat
Abstract : Purpose: The purpose of this paper is to assess level of food safety knowledge and self-reported practices among Lebanese food handlers in Lebanese households and to identify the association between knowledge/practices and socio-demographic characteristics. Design/methodology/approach: A cross-sectional study was conducted among 1, 500 participants from different gender, age, area of residence, income, marital status and education. They completed a questionnaire of six questions about demographics, and 26 questions related to knowledge and self-reported practices in terms of food handling, storage, usage of kitchen facilities and personal hygiene subgroups. SPSS v23 was used for statistical analyses. Student t -test and analysis of variance were conducted. Significance level of 0.05 was used. Findings: On average, participants scored 55.6±16.3, 51.3±25.7, 67.4±19.3 and 89.1±16.3 on food handling, storage, usage of kitchen facilities and personal hygiene, respectively, whereas the passing (score above 50 percent) rates were 64.5, 69.9, 90.5 and 99.1, respectively, for the different subgroups. Gender had significant ( p <0.05) effect on food handling and personal hygiene; age, marital status and education had significant ( p <0.05) effect on handling, usage of kitchen facilities and personal hygiene; area of residence had significant ( p <0.05) effect on storage, handling and usage of kitchen facilities; income had significant ( p <0.05) effect on handling and usage of kitchen facilities. Overall mean food safety knowledge and self-reported practices score was 63.8±12.6; passing rate was 86.2; gender, age, area of residence, education, marital status and income had significant ( p <0.05) effect. Food safety self-reported practices and knowledge scores were significantly ( p <0.001) related to a weak to moderate correlation coefficient ( R =0.34). Practical implications: The results confirm the need for ongoing educational initiatives to improve the relatively low food safety knowledge and practices among the Lebanese food handlers in Lebanese households. Originality/value: No study has determined the food safety knowledge and self-reported practices of Lebanese food handlers in Lebanese households before.